Brain activity and emotional processing in smokers treated with varenicline. (20th April 2011) - Loughead, James; Ray, Riju; Wileyto, E. Paul; Ruparel, Kosha; O'Donnell, Gregory P.; Senecal, Nicole; Siegel, Steven; Gur, Ruben C.; Lerman, Caryn
ABSTRACT Prior evidence suggests that varenicline, an effective smoking cessation treatment, may relieve negative affective signs of nicotine withdrawal. We examined varenicline effects on emotional processing in 25 abstinent smokers after 13 days of varenicline and placebo using a within‐subject cross‐over design. Blood oxygen level dependent (BOLD) functional magnetic resonance imaging was acquired while subjects completed a face emotion identification task. Results showed a significant drug effect, characterized by decreased BOLD signal in dorsal anterior cingulate/medial frontal cortex, occipital cortex and thalamus. Increased BOLD signal was observed in the middle temporal gyrus. Varenicline improved correct response time; however, neither BOLD signal nor performance effects were moderated by emotion type. An exploratory region of interest analysis suggests that varenicline reduced amygdala activity independent of emotional valence. Taken together, these results suggest that observed drug effects on brain activity do not reflect affective changes but rather enhanced early processing of perceptual features of facial stimuli.